Identification and molecular characterization of Staphylococcus aureus and multi‐drug resistant MRSA from monkey faeces in China. Issue 3 (26th December 2019) - Li, Yang; Tang, Yuanyue; Ren, Jingwei; Huang, Jinlin; Li, Qiuchun; Ingmer, Hanne; Jiao, Xinan
Abstract: Staphylococcus aureus is a commensal bacterium and an important opportunistic pathogen in humans and animals. The increase in multi‐drug resistant (MDR) strains of S. aureus is a growing concern due to their impact on animal health and potential for zoonotic transmission. Increasing evidence has shown that MRSA could be transmitted by faeces. The present study determined the prevalence, antibiotic resistance profile and genotypic characteristics of S. aureus isolated from monkey faecal samples in China. Thirty‐eight out of 145 (26.21%) macaque faecal samples were S. aureus positive, which eight (5.5%) isolates were identified as MRSA. Antimicrobial susceptibility tests showed that most of the S. aureus isolates were resistant to tetracycline (TE, 44.74%), followed by penicillin (P, 21.05%), cefoxitin (FOX, 21.05%) and ciprofloxacin (CIP, 18.42%). The predominant spa types were t13638 (44.74%) and t189 (13.16%), which are reported to be closely associated with human infections in China. All MRSA isolates belonged to the SCC mec V type, which six of MRSA isolates were ST3268, while the other two isolates belonged to ST4981. This study for the first time describes the prevalence of S. aureus and MRSA in monkey faeces in China, indicating that faeces could be a potential factor of transmitting S. aureus between humans and monkeys.